2012
DOI: 10.1038/ejcn.2012.189
|View full text |Cite
|
Sign up to set email alerts
|

Effect of daily consumption of probiotic yoghurt on insulin resistance in pregnant women: a randomized controlled trial

Abstract: It is concluded that in contrast to conventional yogurt, daily consumption of probiotic yogurt for 9 weeks maintains serum insulin levels and might help pregnant women prevent developing insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(115 citation statements)
references
References 30 publications
5
107
2
1
Order By: Relevance
“…lactis Bb12 had no effect on blood pressure. Our findings of lack of effect are supported by results of other randomised controlled trials which supplemented with the same combination of probiotic strains [4,29]. As the effects of probiotic bacteria are highly strain specific [17], it is not surprising that studies which supplemented with different probiotic strains and species found different results.…”
Section: Discussionsupporting
confidence: 77%
“…lactis Bb12 had no effect on blood pressure. Our findings of lack of effect are supported by results of other randomised controlled trials which supplemented with the same combination of probiotic strains [4,29]. As the effects of probiotic bacteria are highly strain specific [17], it is not surprising that studies which supplemented with different probiotic strains and species found different results.…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, a significant decrease in serum insulin levels in our previous study in diabetic patients was seen after administration of a synbiotic food containing L. sporogenes (27 × 10 7 CFU) and 1.08 g inulin for 6 weeks compared to the control food [19]. The same findings were reported among type 2 diabetic patients who received L. acidophilus for 4 weeks [29], among patients with T2DM who received multispecies probiotic supplements for 8 weeks [20], and among pregnant women who received 2 strains of L. acidophilus and Bifidobacterium animalis with a total of minimum 1 × 10 7 CFU for 9 weeks [30]. However, some researchers did not find such beneficial effects.…”
Section: Discussionsupporting
confidence: 67%
“…It was found that daily intakes of VDY drink, improved glycemic status of T2DM patients, with or without further calcium content. In another trial conducted on GDM patients, daily consumption of probiotic yoghurt also exhibited beneficial effects on insulin resistance [11] . These previous fruitful trials on both T2DM and GDM have prompted us to investigate the potential effects of VDY drink on GDM women.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in a recent randomized clinical trial, daily consumption of probiotic yoghurt drink was found to have beneficial ef-fect in maintaining serum insulin levels and might help pregnant women prevent developing insulin resistance [11] . To the best of our knowledge, no report has been conducted to assess the effects of vitamin D-supplemented yogurt (VDY) drink on insulin resistance and lipid profiles of pregnant women diagnosed of GDM.…”
Section: Introductionmentioning
confidence: 99%